2010
DOI: 10.1126/science.1186146
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Dysfunction Caused by a K ATP Channel Mutation in Neonatal Diabetes Is Neuronal in Origin

Abstract: Gain-of-function mutations in Kir6.2 (KCNJ11), the pore-forming subunit of the adenosine triphosphate (ATP)-sensitive potassium (KATP) channel, cause neonatal diabetes. Many patients also suffer from hypotonia (weak and flaccid muscles) and balance problems. The diabetes arises from suppressed insulin secretion by overactive KATP channels in pancreatic beta-cells, but the source of the motor phenotype is unknown. By using mice carrying a human Kir6.2 mutation (Val59-->Met59) targeted to either muscle or nerve,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
107
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(119 citation statements)
references
References 20 publications
6
107
0
4
Order By: Relevance
“…Thus, the muscle disorders in patients with KCNJ11 mutations do not seem ascribable to changes in muscle membrane excitability. Furthermore, they are ascribable to the effects of the mutation in central nervous system cells rather than to muscle excitability impairments (33). None of our patients had a history of recurrent severe hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the muscle disorders in patients with KCNJ11 mutations do not seem ascribable to changes in muscle membrane excitability. Furthermore, they are ascribable to the effects of the mutation in central nervous system cells rather than to muscle excitability impairments (33). None of our patients had a history of recurrent severe hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…These range from severe developmental delay and epilepsy diagnosed before 1 year (DEND syndrome) to a milder phenotype known as intermediate DEND syndrome (iDEND) (10). The neurological features are consistent with the expression of mutated K ATP channels in neurons (11). In a minority of cases, the neurological features may be incidental or secondary to complications of diabetes such as ketoacidosis and severe hypoglycaemia (12).…”
Section: Introductionmentioning
confidence: 98%
“…Also, muscle weakness and ataxic gait in a patient with a Kir6.2 mutation was improved by treatment with gliclazide, which interacts only with SUR1 [174] . More definitive evidence comes from a recent study by Clark et al, in which hemizygous mice that selectively express the V59M Kir6.2 mutation in muscle or neurons were examined [172] . Behaviourally, transgenic mice with the neuronal V59M Kir6.2 mutation display the same motor impairments as seen in human DEND.…”
Section: Pathophysiological Role Of K Atp Channels In Glucose Homeo Smentioning
confidence: 99%
“…Neurons, like pancreatic beta-cells, mostly contain www.chinaphar.com Quan Y et al Acta Pharmacologica Sinica npg K ATP channels made up of Kir6.2 and SUR1 subunits, whereas muscle K ATP channels are composed of Kir6.2 and SUR2A subunits. In fact, it has been shown that the Kir6.2 V59M mutation specifically enhances the flow of current through K ATP channels composed of Kir6.2/SUR1 subunits, but has no effect on Kir6.2/SUR2A K ATP channels [172] . Thus, the V59M mutation selectively targets the pancreas and neurons while sparing the muscle.…”
Section: Pathophysiological Role Of K Atp Channels In Glucose Homeo Smentioning
confidence: 99%
See 1 more Smart Citation